Simulation of non-Newtonian flow of blood in a modified laparoscopic forceps used in minimally invasive surgery. Issue 16 (6th December 2021) - Junaidi, Md. Abdul Raheem; Sista, Harsha; Kalluri, Ram Chandra Murthy; Rao, Y. V. Daseswara; Gokhale, Alla Gopala Krishna
Abstract: During surgeries, blood often oozes out of the operated tissue and this has to be sucked out by the S–I device. Blood is more viscous than saline, the cleaning fluid is used in the S–I process. Therefore, for a more comprehensive CFD flow analysis of the improved forceps is simulated in the present work for different driving pressures. The resulting flow rate of blood is compared among the prospective designs and the S–I device currently in use. The new surgical forceps eliminates re-insertion of dissector with suction-irrigator and is reusable, multi-functional, non-toxic, corrosion resistant, toughened, and cost-effective.